A grande imprensa versus a escola pública: quando a notícia cria “verdades” por meio da sanção simbólica - Romboli, Magali Seravalli (2023)
The present dissertation, entitled “Mass Media versus Public School: when the news creates ¨truths¨ through symbolic sanction, aims to investigate and analyze the symbolic sanction that the mass media “naturalizes” in the social and historical context of students, families, educators of public schools, by reporting results of institutional evaluations of Basic Education in public schools, as if they were documentaries. The problem that stimulated this research was the concern with the “naturalness” of journalistic statements, when relating children and adolescents from public schools as “those who do not know how to do simple math" and "who are illiterate", for studying in bad schools. The hypothesis is based on the observation that, the more the mainstream press “naturalizes” these documentaries, the more it strengthens the symbolic sanction that the public school is not of quality. The theoretical framework is based on the concept of evaluation typology, by José Eustáquio Romão (1998); symbolic power, by Pierre Bourdieu (1989) and education as a practice of freedom, by Paulo Freire (1967). It was considered mass media, the one with the greatest national coverage, audience and revenue, being the monopoly of only four large Brazilian families. From the methodological point of view, a quantitative and qualitative approach will be used, using as procedures interviews with students, teachers and families, in addition to document analysis.